Bali Belly: Salmonella senftenberg Found in an Infected Ovarian Endometrioma - P. D. M. Pathiraja; Junaid Rafi; Emily Woolnough; Anna Clare (Case Reports in Obstetrics and Gynecology)
Salmonella is an extremely rare cause of an infected endometrioma. We present a case of a 30-year-old immunocompetent woman presenting with fevers and abdominal pain, on a background of prior endometriosis. Initial antibiotic treatment for pelvic inflammatory disease failed, and the patient progressed to septic shock requiring surgical evacuation of an infected ovarian endometrioma. Microbiological samples from stool, ovary, and peritoneal fluid revealed infection with Salmonella senftenberg. The likely diagnosis was Salmonella enterocolitis with bacterial translocation to an ovarian endometrioma.